FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN PRAKTIK PENGELOLAAN LIMBAH MEDIS PADAT PUSKESMAS CAWAS I KABUPATEN KLATEN - Pegi Fatma Okneta Sari; Sulistyani Suliastyani; Aditya Kusumawati (Fakultas Kesehatan Masyarakat Universitas Diponegoro, 2018)
Community Health Center’s (CHC) medical waste if not managed properly can cause health and environmental problems. Proper knowledge of health care workers, positive attitudes and safe practices on solid medical waste management are the most important because healthcare workers have the highest risk of infection with hepatitis and HIV. The purpose of this research was to analyze the relationship characteristics, the level of knowledge, and attitudes of healthcare workers with practices of solid medical waste management in Cawas I CHC, Klaten Regency. This research was an observational analytic research with cross sectional approach. The affordable population in this study were 31 workers who produced and or conducted solid medical waste segregation and packaging at Cawas I CHC. A total of 31 healthcare workers were included in this study using total sampling. Data collection using questionnaires and observation sheets. Data analysis using Spearman correlation test. The results of this research showed that 71% of healthcare workers are the adult age group, 90% have higher education (associate degree and bachelor), 71% have a long working period (more than ten years), 71% have good knowledge, 71% have good attitude and 61.3% have good practices. The attitude variable is related to practices (p-value=0.042) while the age variable (p-value=0.455), level of education (p-value=0.311), work experience (p-value=0.174) and level of knowledge (p-value =0.076) are not related to practices. Based on this research, there is a correlation between attitudes of healthcare workers with practices of solid medical waste management in Cawas I CHC, Klaten Regency.